Use of a palladium(II)-catalyzed oxidative kinetic resolution in synthetic efforts toward bielschowskysin - Meyer, Michael E. (2013)
Progress toward the cyclobutane core of bielshowskysin is reported. The core was thought to arise from a cyclopropane intermediate via a furan-mediated cyclopropane fragmentation, followed by a 1,4-Michael addition. The synthesis of the cyclopropane intermediate utilizes a Suzuki coupling reaction, an esterification with 2-diazoacetoacetic acid, and a copper catalyzed cyclopropanation. An alcohol intermediate within the synthetic route was obtained in high enantiopurity via a highly selective palladium(II)-catalyzed oxidative kinetic resolution (OKR).